Dietary Weight-Loss and Exercise Effects on Insulin Resistance in Postmenopausal Women - Mason, Caitlin (2011)
BACKGROUND: Comprehensive lifestyle interventions are effective in preventing diabetes and restoring glucose regulation; however, the key stimulus for change has not been identified and effects in older individuals are not established. The aim of the study was to investigate the independent and combined effects of dietary weight-loss and exercise on insulin sensitivity and restoration of normal fasting glucose in mid-aged and older women. DESIGN: Four-arm RCT, conducted between 2005 and 2009 and data analyzed in 2010. SETTING/PARTICIPANTS: 439 inactive, overweight/obese postmenopausal women. Interventions: Women were assigned to: dietary weight loss (n=118), exercise (n=117), exercise+diet (n=117), or control (n=87). The diet intervention was a group-based reduced-calorie program with a 10% weight-loss goal. The exercise intervention was 45 min/day, 5 days/week of moderate-to-vigorous intensity aerobic activity. MAIN OUTCOME MEASURES: 12-month change in serum insulin, C-peptide, fasting glucose, and whole body insulin resistance (HOMA-IR). RESULTS: A significant improvement in HOMA-IR was detected in the diet (−24%, p<0.001) and exercise+ diet (−26%, p<0.001) groups, but not in the exercise (−9%, p=0.22) group compared to controls (−2%); these effects were similar in middle-aged (50–60 years) and older women (aged 60–75 years). Among those with impaired fasting glucose (5.6–6.9 mmol/L) at baseline (n=143; 33%), the odds (95% CI) of regressing to normal fasting glucose after adjusting for weight loss and baseline levels were: 2.5 (0.8, 8.4), 2.76 (0.8, 10.0), and 3.1 (1.0, 9.9) in the diet, exercise+diet, and exercise group, respectively, compared to controls. CONCLUSIONS: Dietary weight loss, with or without exercise, significantly improved insulin resistance. Older women derived as much benefit as did the younger postmenopausal women.